Scrotal trauma: interest of preoperative ultrasound in the prediction of the rupture of the tunica albuginea - Stefano Manno; Antonio Cicione; Lorenzo Bagalà; Antonio Catricalà; Piero Ronchi; Simona Tiburzi; Carolina Giannace; Lucio Dell’Atti (Medicinski glasnik, 2020)
Aim: Scrotal bruises are quite frequent injuries affecting young subjects, with psychological repercussions on body image and fertility. The interest of ultrasound in the context of the emergency remains controversial. The aim of our study was to investigate clinical, ultrasonographic and operative features of scrotal contusions, and to evaluate the contribution of ultrasound in the description of traumatic lesions. Methods: In this retrospective and descriptive study 71 scrotal contusions operated from December 2015 to April 2020 were collected. We retrospectively analysed 26 patients (aged between 14 and 79 years) of 71 who sustained a scrotal ultrasound, where the latter was positive. The primary endpoint was albuginea rupture, whose concordance between ultrasound and surgery was assessed using the Kappa method. Positive and negative predictive values, sensitivity and specificity for the presence of albuginea rupture were evaluated for a set of ultrasound data: scrotal haematoma, haematocele, regularity of testicular contours, testicular fracture (specificity (93%), testicular haematoma, and Doppler signal intensity. Results: Surgical treatment was necessary in 26 (37%) patients; only six orchiectomy were performed. Surgical exploration should be performed if haematocele is found in the genital examination without any ultrasound complement. Conclusion: The ultrasonography is useful, detailed and accurate when the haematocele is not clinically evident.
Keywords: genital; injuries; testicular; ultrasound